CHARACTERIZATION OF VEGETATION COVER AND LAND USE WITHIN THE BUFFER ZONE OF COPEY RIVER, JACÓ, PUNTARENAS, COSTA RICA - Mattey Trigueros, David (2017)
Rivers are considered one of the ecosystems most affected by humans. This is why it is important to evaluate the conditions of rivers and their environment. The purpose of this research is to characterize the vegetation cover and land use within the buffer zone along the Copey river. In two field trips (2013) we hit the river course to generate control geopositioned points coverage, vegetation variations and photographing. Then, we used the photo-interpretation method, by the expert judgment, and then generated three coverage maps. Additionally, we generated DAP, characterization height of trees in tree river zones. We categorized 11 coverage types, where the predominant coverage was the dense forest. The upper side is the one with the greatest forest cover. Shrubby grasslands edge predominates in the middle side, and the lower side begins to present urban infrastructure. We concluded that there is a large area devoid of vegetation, without urban infrastructure, which indicates that it is one of the areas with the greatest potential for restoration efforts.